Local ideas about rights of common in the context of a historical transformation from commons to private property - Erling Berge; Anne Sigrid Haugset (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
More than 200 years after the King sold one of the "King's commons" (Follafoss, located in the current Verran municipality) to urban timber merchants, local people in some ways still behave as if the area is a kind of commons. The paper will outline the history of the transformation of the area from an 18th century King's commons to a 21th century battleground for ideas about ancient access and use rights of community members facing rights of a commercial forest owner and the local consequences of national legislation. This battleground will be illuminated by the answers that current users provide to questions about what they believe their rights of access and use are. We shall in particular look for differences between what people believe and what the law seems to say about rights and duties in the Follafoss area.
Keywords: P48; Q15; 330; King's commons; private forest; rights of common; customary rights; national legislation; loss of customary rights